Asymmetry of ECOWAS integration process: contribution of regional hegemon and small country - Omo-Ogbebor, D.O.; Sanusi, A.H. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
This article deals with the role of Nigeria and Ghana in ECOWAS specific fields of integration since its creation in 1975. It showed the relevance of Nigeria as a regional leader and the importance of Ghana as a key factor in ECOWAS integration process, and their respective foreign policy stand towards West African integration process in the present century. In order to evaluate and present the role of Nigeria and Ghana in ECOWAS integration process, the authors set out three main tasks to actualize it. The first task is to identify the main areas of ECOWAS integration process, namely: economic integration, security formation and political reformation using qualitative methodological analysis to achieve this task. The second task is the review of ECOWAS operational structure, which explained how Nigeria was able to exert its hegemony status in ECOWAS, and how Ghana is able to remain useful in ECOWAS despite the overwhelming influence of Nigeria. The third task is using historical analytical method to present facts and explain the various contributions by Nigeria and Ghana in ECOWAS economic liberation process, peacekeeping operations, and political interventions in ECOWAS member states which have brought relative peace and security to the region. The authors draw conclusion based on the result of the research analysis that, in spite of ECOWAS compositions which include the Francophone countries in the region and its leadership structure, Nigeria and Ghana have led by example, by devoting much attention and commitment to the ECOWAS integration process through mediations, peacekeeping, political intervention and economic cooperation.